Hyrological modelling using HEC-HMS for Kuantan River Basin - Ahmad Amiruddin, Mohammad Shabri (2018)
Unusual heavy rain that happens during Northeast monsoon between November to March may lead severe flood to the east coast of Peninsular Malaysia, including Kuantan River. This phenomenon gives a great impact to human being, can cause major damage to properties and may reduce the quality of human health. Hence, an attempt has been made to mitigate the impact of flooding using modelling approach. The application of Hydrologic Engineering Centre Hydrology Modelling System (HEC-HMS) software was used to estimate the flow hydrograph of Kuantan River Basin. The objectives are to develop a calibrated and validated rainfall-runoff model for Kuantan River Basin using HEC-HMS and to predict the peak flow and produce hydrograph for 2012 Kuantan flood event. The model was calibrated and validated using historical observed data that were taken from Department of Irrigation and Drainage (DID). Event dated 04th September 2010 to 09th September 2010 was used in model calibration and two events dated 01st September 2010 to 06th September 2010 and 22nd February 2011 to 27th February 2011 respectively were used for validation process. Clark UH method was used to transform excess rainfall, whereby SCS Curve Number method was applied for calculating the losses and for estimating base flow, Constant Monthly method was used. Nash-Sutcliffe model efficiency was used to verify the model calibration and validation. The model efficiency for calibrated and validated model is 0.81 and 0.80 and 0.70 respectively, which is acceptable.